Birdwatching preferences reveal synergies and tradeoffs among recreation, carbon, and fisheries ecosystem services in Pacific Northwest estuaries, USA - Kristin B. Byrd; Isa Woo; Laurie Hall; Emily Pindilli; Monica Moritsch; Anthony Good; Susan De La Cruz; Melanie Davis; Glynnis Nakai (Ecosystem Services, 2024)

Societal benefits of floodplains in the Chesapeake Bay and Delaware River watersheds: Sediment, nutrient, and flood regulation ecosystem services - Kristina G. Hopkins; Jacqueline S. Welles; Emily J. Pindilli; Gregory B. Noe; Peter R. Claggett; Labeeb Ahmed; Marina J. Metes (Journal of Environmental Management, 2023)

Trends in biodiversity and habitat quantification tools used for market‐based conservation in the United States - Scott J. Chiavacci; Emily J. Pindilli (Conservation Biology, 2020)
Market‐based conservation mechanisms are designed to facilitate the mitigation of harm to and conservation of habitats and biodiversity. Their potential is partly hindered, however, by the quantification tools used to assess habitat quality and functionality. Of specific concern are the lack of transparency and standardization in tool development and gaps in tool availability. To address these issues, we collected information via internet and literature searchers and through conversations with tool developers and users on tools used in U.S. conservation mechanisms, such as payments for ecosystem services (PES) and ecolabel programs, conservation banking, and habitat exchanges. We summarized information about tools and explored trends among and within mechanisms based on criteria detailing geographic, ecological, and technical features of tools. We identified 69 tools that assessed at least 34 species and 39 habitat types. Where tools reported pricing, 98% were freely available. More tools were applied to states along the U.S. West Coast than elsewhere, and the level of tool transferability varied markedly among mechanisms. Tools most often incorporated conditions at numerous spatial scales, frequently addressed multiple risks to site viability, and required 1–83 data inputs. Most tools required a moderate or greater level of user skill. Average tool‐complexity estimates were similar among all mechanisms except PES programs. Our results illustrate the diversity among tools in their ecological features, data needs, and geographic application, supporting concerns about a lack of standardization. However, consistency among tools in user skill requirements, incorporation of multiple spatial scales, and complexity highlight important commonalities that could serve as a starting point for establishing more standardized tool development and feature‐incorporation processes. Greater standardization in tool design may expand market participation and facilitate a needed assessment of the effectiveness of market‐based conservation.